KOMUNIKASI DALAM PERSPEKTIF FILSAFAT DAN IMPLIKASINYA TERHADAP BIMBINGAN DAN KONSELING - Nurroh Maya; Akhmad Fajar Prasetya (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2026)
This study discusses communication from a philosophical perspective and its implications for guidance and counselling practices. This study is motivated by the fact that communication is often understood explicitly as a technical skill in the counselling process, but philosophically, communication has a deeper dimension as a means of forming dialogical and reflective human relationships. Through a literature review approach, this study examines concepts, theories, and research results that explain the role of communication as the main foundation of effective counselling relationships. The results of the study show that the success of counselling is determined more by the quality of the relationship built through meaningful, empathetic, and open communication than by mastery of intervention techniques. A philosophical approach to communication encourages counsellors to be reflective and humanistic, and to respect counselees as individuals with their own personalities and life experiences. Thus, communication in counselling functions not only as a technical skill, but as a means of transformation towards self-understanding